2015
DOI: 10.1016/j.cell.2015.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Staphylococcus aureus Cas9

Abstract: SUMMARY The RNA-guided DNA endonuclease Cas9 cleaves double-stranded DNA targets with a protospacer adjacent motif (PAM) and complementarity to the guide RNA. Recently, we harnessed Staphylococcus aureus Cas9 (SaCas9), which is significantly smaller than Streptococcus pyogenes Cas9 (SpCas9), to facilitate efficient in vivo genome editing. Here, we report the crystal structures of SaCas9 in complex with a single guide RNA (sgRNA) and its double-stranded DNA targets, containing the 5′-TTGAAT-3′ PAM and the 5′-TT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
440
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 379 publications
(475 citation statements)
references
References 41 publications
18
440
1
6
Order By: Relevance
“…In contrast, the Cas9 phosphate lock loop interaction with the target strand +1 phosphate is linked to target DNA/sgRNA pairing immediately upstream of PAM but does not play a significant role in the initial duplex destabilization. Thus, the Cas9/sgRNA interactions with PAM-proximal sequences of DNA probes not complementary to sgRNA studied here differ from those interactions revealed in crystal complexes, where the target DNA strand was hybridized with the complementary sgRNA (16,(26)(27)(28). Overlays of Cas9/sgRNA-DNA and Cas9/sgRNA structures reveal that in the Cas9/sgRNA structure, domains 2 and 3 of the helical recognition lobe sterically occlude the central channel in which the RNA/DNA hybrid is located in the Cas9/sgRNA-DNA complexes (16,21,26).…”
Section: Discussionmentioning
confidence: 54%
“…In contrast, the Cas9 phosphate lock loop interaction with the target strand +1 phosphate is linked to target DNA/sgRNA pairing immediately upstream of PAM but does not play a significant role in the initial duplex destabilization. Thus, the Cas9/sgRNA interactions with PAM-proximal sequences of DNA probes not complementary to sgRNA studied here differ from those interactions revealed in crystal complexes, where the target DNA strand was hybridized with the complementary sgRNA (16,(26)(27)(28). Overlays of Cas9/sgRNA-DNA and Cas9/sgRNA structures reveal that in the Cas9/sgRNA structure, domains 2 and 3 of the helical recognition lobe sterically occlude the central channel in which the RNA/DNA hybrid is located in the Cas9/sgRNA-DNA complexes (16,21,26).…”
Section: Discussionmentioning
confidence: 54%
“…Structural comparison of available structures of Cas9 orthologs, including the apo structure of Actinomyces naeslundii Cas9 (AnaCas9) from subtype II-C (50) and the DNA-bound structures of SaCas9 (73) and FnCas9 (34), reveals a relatively conserved catalytic core and a highly conserved characteristic arginine-rich bridge helix, as well as the least conserved alpha-helical REC lobe essential for guide RNA binding and a divergent CTD that is responsible for both the PAM recognition and the guide RNA repeat-antirepeat heteroduplex binding (Figure 7b-f ), which explains their distinct PAM specificities and orthologous sgRNA recognition and further enhances our understanding of the structural conservation and divergence among the CRISPR-Cas9 systems. Intriguingly, similar to SpyCas9, both SaCas9 and FnCas9 employ the phosphate lock loop to stabilize the +1 phosphate in the target DNA strand and specifically recognize the major groove of the PAM-proximal duplex via arginine-mediated basespecific interactions (Figure 7d, f ), suggesting the conserved RNA-guided DNA targeting and cleavage mechanisms across the CRISPR-Cas9 systems (34,73).…”
Section: Figurementioning
confidence: 99%
“…CRISPR-Cas9 has been extensively used for genome editing in various cell types and organisms [11,12]. A series of structural studies of Streptococcus pyogenes Cas9 (SpyCas9) and its orthologs have revealed the detailed intermolecular interactions, as well as the conformational changes among different substrate-bound states [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%